2018
DOI: 10.1007/s00101-018-0431-8
|View full text |Cite
|
Sign up to set email alerts
|

Der Herzkathetertisch ist nicht der OP-Tisch

Abstract: An elevated pulmonary pressure obtained preoperatively during right heart catheterization is not indicative of an elevated pulmonary pressure either intraoperatively or postoperatively. There are various explanations for the differences (e.g., different physiological and pathophysiological settings, such as sedation with potential hypercapnia versus anesthesia with vasodilation when measured; newly prescribed medication coming into effect between the right heart catheterization and surgery; intraoperative posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Bias informs about accuracy, and agreement informs about precision. Previous studies demonstrated that the inherent instability and/or interventions (e.g., diuretics) that occur between studies could have influenced the findings ( 35 , 36 ). Our hypothesis was that medication taken before to RHC may reduce the risk of RHC in patients with severe PH (US-PASP >70 mmHg), and may be the main reason for the bias and agreement gap between TR-SQG III and IV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bias informs about accuracy, and agreement informs about precision. Previous studies demonstrated that the inherent instability and/or interventions (e.g., diuretics) that occur between studies could have influenced the findings ( 35 , 36 ). Our hypothesis was that medication taken before to RHC may reduce the risk of RHC in patients with severe PH (US-PASP >70 mmHg), and may be the main reason for the bias and agreement gap between TR-SQG III and IV.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the shorter measurement time intervals between TTE and RHC after BPA. Although patients with PH may experience with spontaneous fluctuations in up to 22% for PAMP and 36% for PVR within only a few hours ( 36 ). Ni et al ( 15 ) demonstrated that shortening the time interval between TTE and RHC could improve the accuracy of TTE and the diagnostic accuracy was the highest when the time period was less than or equal to 24 hours.…”
Section: Discussionmentioning
confidence: 99%